AIRLINE ITINERARY CHOICE IN A DYNAMIC SUPPLY ENVIRONMENT: RESULTS FROM A STATED PREFERENCE SURVEY - Freund-Feinstei, Uzi; Bekhor, Shlomo (Journal of Tourism, Sustainability and Well-being, 2017)
This paper investigates the choice of airline itineraries in dynamic settings using a tailored stated preference survey. The paper hypothesizes that airline itinerary choice is not a one-time event, but a continuous process during a certain time frame. Consumers can choose either to purchase an itinerary, deferring choice up to the end of the sales period, or completely declining the purchase. Understanding such consumers’ behavior is specifically relevant to the tourism industry, where firms are extensively utilizing internet websites to offer their products (e.g., airline tickets, hotel rooms) to consumers. The paper describes the stated preference survey with real itineraries of various airlines on medium and long-haul routes. Choice sets are composed with dynamic and static variables and socio-economic variables. Questionnaires were distributed electronically among various groups of respondents, yielding a sample of 914 persons. Results show that (i) itinerary choice deferring takes place, with differences between tourists and business-travelers, (ii) the decision whether to defer choice is affected by dynamically changing variables and by the length of each respondent’s allocated choice period, and (iii) the proposed methodology is adequate for investigating choice in dynamic settings and thus indicating its potential for further research in transportation planning and in tourism.